2010
DOI: 10.1111/j.1460-9568.2010.07292.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct synaptic properties of perisomatic inhibitory cell types and their different modulation by cholinergic receptor activation in the CA3 region of the mouse hippocampus

Abstract: Perisomatic inhibition originates from three types of GABAergic interneurons in cortical structures, including parvalbumin-containing fast-spiking basket cells (FSBCs) and axo-axonic cells (AACs), as well as cholecystokinin-expressing regular-spiking basket cells (RSBCs). These interneurons may have significant impact in various cognitive processes, and are subjects of cholinergic modulation. However, it is largely unknown how cholinergic receptor activation modulates the function of perisomatic inhibitory cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
119
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 87 publications
(135 citation statements)
references
References 58 publications
16
119
0
Order By: Relevance
“…5 and 6; Table 3). This finding agrees well with data on physiological properties of these cells that are also more similar to PV-positive basket cells [fast-spiking properties with moderate accommodation and reliable transmission (Maccaferri et al, 2000;Szabó et al, 2010)]. …”
Section: Pv-positive Terminals Have Relatively Larger Mitochondriasupporting
confidence: 82%
See 4 more Smart Citations
“…5 and 6; Table 3). This finding agrees well with data on physiological properties of these cells that are also more similar to PV-positive basket cells [fast-spiking properties with moderate accommodation and reliable transmission (Maccaferri et al, 2000;Szabó et al, 2010)]. …”
Section: Pv-positive Terminals Have Relatively Larger Mitochondriasupporting
confidence: 82%
“…The mIPSC amplitude depends predominantly on the number of postsynaptic receptors that are proportional to the size of the synapses (Nusser et al, 1997), therefore, higher variability of the size of different synapses of CB 1 -positive somatic boutons may provide an anatomical basis for their highly variable quantal events. Several studies showed that synaptic connections between PV-positive basket cells and pyramidal cells are much more reliable than connections between CCK/CB 1 -positive basket cells and pyramidal cells, in the latter of which connection failures of synaptic transmission are frequent (Hefft and Jonas, 2005;Daw et al, 2009;Szabó et al, 2010). These observations are not easily explained, because boutons with larger synaptic area are generally considered to be more efficient and faithful (Pierce and Lewin, 1994;Holderith et al, 2012).…”
Section: Pv-positive Terminals Have Relatively Larger Mitochondriamentioning
confidence: 72%
See 3 more Smart Citations